Plasma citrulline is a sensitive safety biomarker for small intestinal injury in rats. (1st October 2018) - Saitoh, Wataru; Takada, Sanae; Hirao, Jun; Shirai, Makoto; Iguchi, Takuma; Tsuji, Makoto; Nishiya, Takayoshi; Mori, Kazuhiko
Highlights: Irinotecan induced slight single cell necrosis in the small intestine. Decreased plasma citrulline was seen along with the lesions. Expression of genes for citrulline synthesis was reduced in the small intestine. Citrulline and arginine levels in the ileum were decreased. Reduced plasma citrulline and arginine were evident among endogenous metabolites. Abstract: Plasma citrulline is decreased in cases of severe intestinal injury with apparent villus and cellular atrophy. However, the fluctuation of plasma citrulline in slight intestinal injury remains to be investigated. To clarify this, irinotecan at 30 mg/kg or 60 mg/kg was administered intravenously to rats. Irinotecan reduced plasma citrulline concentrations compared to those in the pair-fed control, being concurrent with slight single cell necrosis and mucosal epithelium regeneration in the small intestine without apparent villus and cellular atrophy. Gene expression of enzymes converting glutamine to citrulline was decreased in the small intestine of the injury model. Moreover, citrulline and arginine levels in the ileum were decreased without alterations to glutamine and glutamate levels, indicating that citrulline synthesis from glutamine was impaired. Metabolome analysis revealed that plasma citrulline and arginine levels were decreased, while there were no marked alterations in other amino acids, metabolites of glycolysis, ketone bodies, or fatty acids. These results suggested that a decreased plasma citrulline level was unlikely to result from amino acid catabolism in response to malnutrition. In conclusion, plasma citrulline concentration reflects slight intestinal injury without apparent villus and cellular atrophy, and thus, it would be a sensitive biomarker for the small intestinal injury.